Lived Experiences of First Batch of Returned IDPs in Marawi City: A Post-Conflict Scenario - Abdul Fatah Sarangani (Randwick International of Social Science Journal, 2022)
This study focused on the experiences of the first group of returned internally displaced people to be sheltered in Sagonsongan Temporary Shelters two years prior. Triangulation approach were employed to obtain data using a cross-sectional survey and simple random sampling. 221 important informants participated in the study. The objective of this study was to assess IDPs’ situation on the ground. In general, this study discovered three major issues that IDPs consistently faced: health and nutrition, livelihood, and sanitation. It was revealed that IDPs infrequently received dietary and health-related support and asserted confidently that they only received generic and 'not' healthy food products such as sardines, low-quality rice, and low-cost beans. Also, the shelter lacked adequate medical facilities and personnel to address the medical needs of IDPs, especially during emergencies. The drainage system was a potential source of dengue, leptospirosis, and other pathogens that pose a risk to human health due to its inadequate design, which inhibits precipitation from draining. Moreover, it was revealed that there was a lack of and insufficient livelihood support in the shelter. Capacity building was also a mismatch because there was no technical job available following the training. Hence, the relocation area is not conducive to sustaining a livelihood. In addition, it was determined that the level of sanitation in the shelter differs from one area to the next. Nevertheless, garbage disposal management in the area is often inadequate. As a result of inefficient waste management and an unhealthy environment, cockroaches, flies, and mosquitoes thrive